2019
DOI: 10.3389/fmars.2019.00135
|View full text |Cite
|
Sign up to set email alerts
|

Satellite Remote Sensing in Shark and Ray Ecology, Conservation and Management

Abstract: Global elasmobranch populations have declined dramatically over the past 50 years, and continued research into the drivers of their habitats and distributions is vital for improved conservation and management. How environmental factors influence elasmobranch behavior, habitat use, and movement patterns is still relatively poorly understood, in part because of the scale over which many of these animals roam and the remote nature of the marine ecosystems they inhabit. In the last decade there has been an explosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 211 publications
(298 reference statements)
1
25
0
Order By: Relevance
“…As a result, in 2015 the status of M. asterias was upgraded from "Least Concern" to "Near Threatened" (Nieto et al, 2015). This justifies the prioritization of studies on behaviour, habitat use and movement patterns (Williamson et al, 2019). Brevé et al (2016), using a mark-recapture programme, showed indications of seasonal migration F I G U R E 1 Legend on next page.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…As a result, in 2015 the status of M. asterias was upgraded from "Least Concern" to "Near Threatened" (Nieto et al, 2015). This justifies the prioritization of studies on behaviour, habitat use and movement patterns (Williamson et al, 2019). Brevé et al (2016), using a mark-recapture programme, showed indications of seasonal migration F I G U R E 1 Legend on next page.…”
mentioning
confidence: 70%
“…As a result, in 2015 the status of M. asterias was upgraded from “Least Concern” to “Near Threatened” (Nieto et al ., 2015). This justifies the prioritization of studies on behaviour, habitat use and movement patterns (Williamson et al ., 2019). Brevé et al .…”
Section: Figurementioning
confidence: 99%
“…Due to time constraints in territory and the area covered by each of our receivers, our analyses currently do not integrate information about the environmental variables at each monitoring station (i.e. node covariates); further research that incorporates high‐resolution satellite remotely sensed environmental data will be important for exploring the drivers of reef shark movements in these remote locations (Williamson, Tebbs, Dawson, & Jacoby, 2019). That said, a recent study exploring the bleaching and recovery of the scleractinian coral reef communities within BIOT during the consecutive, temperature‐driven mortality events of 2015 and 2016 (Head et al., 2019), showed that our predicted ecological hotspots had lower percentage change in coral cover in response to warming events (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although food may be a primary driver of temporal changes in movement, factors such as thermoregulation and predator avoidance, and environmental variables such as sea surface temperature, salinity and current, have been found to also drive temporal changes in movement (91,108). Despite recent developments to our understanding of how environmental variables effect elasmobranch movement (108,109), they are still relatively poorly understood, and investigations should be undertaken to further explore their impact on both spatial and temporal aspects of elasmobranch movement in this region.…”
Section: Discussionmentioning
confidence: 99%